Prevalence and Impacts of Musculoskeletal Pain among the Elderly Living in The East Coast Region of Peninsular Malaysia - Che Hasan, Muhammad Kamil; Asmera, Nur Nabila Izzati; Sulaiman, Suliza; Nurumal, Mohd Said; Nik Mohd Hatta, Nik Noor Kaussar (Makara Journal of Health Research, 2021)
Background: Musculoskeletal pain commonly affects the elderly, but the extent of this problem within the Malaysian community remains unknown. This study aimed to investigate the prevalence and impact of musculoskeletal pain among the elderly living in the community. Methods: Elderly individuals aged 60 years and above with musculoskeletal pain and intact cognition were recruited for this study. Musculoskeletal pain was scored using the Nordic Musculoskeletal Questionnaire, and functional ability was assessed via the Lawton Instrumental Activities of Daily Living scale. Mental wellbeing was evaluated using the Short Warwick–Edinburgh Mental Wellbeing scale, and risk of falling was determined via the Short Falls Efficacy Scale – International. Results: A total of 216 community-dwelling elderly individuals participated in this research. Knee pain was the most common pain type experienced by the participants in the past 12 months (58.8%) and 7 days (28.8%). This type of pain was also the most common reason cited by the elderly for their difficulty in working. Age, gender, and body mass index were not significant predictors of musculoskeletal pain in the elderly (p > 0.05). Conclusions: Musculoskeletal pain significantly impacts the functional ability and fear of falling of elderly individuals in the east-coast region of Malaysia. Mental wellbeing scores indicated a decreasing trend, but no significant difference was noted.